Sophoridine Inhibits the Tumour Growth of Non-Small Lung Cancer by Inducing Macrophages M1 Polarisation via MAPK-Mediated Inflammatory Pathway - Zhao, Bei; Hui, Xiaodan; Zeng, Hairong; Yin, Yinan; Huang, Jian; Tang, Qingfeng; Ge, Guangbo; Lei, Tao (Frontiers in Oncology, 2021)
Lung cancer is one of the most common and lethal neoplasms for which very few efficacious treatments are currently available. M1-like polarized tumour-associated macrophages (TAMs) are key mediators to modulate the tumor microenvironment, which play a key role in inhibiting cancer cell growth. Sophoridine, a naturally occurring alkaloid, exerts multiple pharmacological activities including anti-tumour and anti-inflammatory activities, but it has not been characterized as a regulator of tumor microenvironment towards NSCLC. Herein, the regulatory effects of sophoridine on the polarization of THP-1 cells into TAMs and the anti-tumour effects of sophoridine-stimulated M1 polarized macrophages towards lung cancer cells were carefully investigated both in vitro and in vivo. The results showed that sophoridine could significantly promote M1 polarization of RAW264.7 and THP-1-derived macrophages, leading to increased expression of pro-inflammatory cytokines and the M1 surface markers CD86 via activating MAPKs signaling pathway. Further investigations showed that sophoridine-stimulated RAW264.7 and THP-1-derived M1 macrophages effectively induced cell apoptosis as well as inhibited the cell colony formation and cell proliferation in both H460 and Lewis lung cancer cells. In Lewis-bearing mice model, sophoridine (15 or 25 mg/kg) significantly inhibited the tumour growth and up-regulated the expression of CD86/F4/80 in tumour tissues. Collectively, the findings clearly demonstrate that sophoridine promoted M1-like polarization in vitro and in vivo, suggesting that sophoridine held a great therapeutic potential for treating lung cancer.